2017
DOI: 10.3342/kjorl-hns.2017.00451
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Methods for Collecting Saliva for Pepsin Detection in Patients with Laryngopharyngeal Reflux

Abstract: Background and ObjectivesZZTo compare the simple spitting method and the Salivette ® method of collecting saliva for detecting pepsin in patients with laryngopharyngeal reflux disease (LPRD). Subjects and MethodZZThirty-two patients diagnosed with LPRD by 24 hour multichannel intraluminal impedance and pH monitoring were enrolled prospectively. The amounts of pepsin in saliva determined by the simple spitting method and the Salivette ® method were compared. ResultsZZSimple spitting showed higher sensitivity, s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 19 publications
0
4
0
Order By: Relevance
“…The method of saliva sample collection has been well validated [33]. The total number of saliva samples analysed for pepsin in the current multicentre study was 2927 and the best time for collecting saliva samples for salivary pepsin analysis has been answered in the current study with the post-prandial saliva collection time showing the greatest pepsin prevalence.…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…The method of saliva sample collection has been well validated [33]. The total number of saliva samples analysed for pepsin in the current multicentre study was 2927 and the best time for collecting saliva samples for salivary pepsin analysis has been answered in the current study with the post-prandial saliva collection time showing the greatest pepsin prevalence.…”
Section: Discussionmentioning
confidence: 83%
“…This area remains controversial and even using this battery of diagnostic tests is not considered to be accurate [27][28][29]. Recently, several studies have suggested that pepsin is a good biomarker for detecting LPR and that it can be considered as a reliable diagnostic marker [30][31][32][33][34][35][36][37]; this in turn has led to a valuable role for pepsin as a diagnostic test for both GERD and LPR [1,[38][39][40][41] especially as Peptest is a rapid and non-invasive diagnostic test and patient compliance has been demonstrated to be high. This in turn suggests Peptest as an interesting alternative to the other more invasive diagnostic tests including the current gold standard.…”
Section: Discussionmentioning
confidence: 99%
“…A specific device (“Salivette system”—SARSTEDT D‐51588‐Numbrecht) was used to collect saliva 6 . Patients were asked to keep the sterile tampon under their tongue for 15 minutes; patients were also asked to clear saliva from the back of their throat and spit into the same tube with the tampon to increase the chance of detecting proximal reflux components (pepsin, bile acids) as described by Ryu et al (2017) 7 …”
Section: Methodsmentioning
confidence: 99%
“…6 Patients were asked to keep the sterile tampon under their tongue for 15 minutes; patients were also asked to clear saliva from the back of their throat and spit into the same tube with the tampon to increase the chance of detecting proximal reflux components (pepsin, bile acids) as described by Ryu et al (2017). 7 Samples were retrieved, centrifuged, divided in aliquots and stored at −80°C. We found no significant differences in total salivary volume collected with the technique.…”
Section: Saliva Collectionmentioning
confidence: 99%